Liquidity and Profitability of Low and High Turnover Commercial Banks in Nepal - Goet, Jogindar (Management Dynamics, 2021)
This paper explores the effect of several bank-specific variables, including capital and liquidity, on the profitability of listed commercial banks operating in Nepal. Factors of banks’ profitability like net profit ratio, return on assets, and return on equity have been assessed by the panel data (10 observations) of six listed banks out of twenty-seven banks. In this study, liquidity has been quantified in regulatory capital, loan and advance to total deposit, liquid assets to total assets, liquid assets to total deposit, and cash reserve ratio. This study found a significant correlation between liquidity variables and profitability variables. Again, it has been shown that the cash reserve ratio significantly impacts the net profit ratio, return on assets, and equity. Likewise, loan and advance to total deposit, liquid assets to total assets, and liquid assets to total deposit have no significant impact on the selected banks’ net profit ratio, return on assets, and return on equity.